Assessment of growth and management of the clam galatea paradoxa fishery at the lower Volta, Ghana - Amedzro, Jerry John (2016)
A thesis submitted to the Department of Fisheries and Watershed Management in partial fulfillment of the requirements for the award of the degree of Master of Philosophy (MPhil.) in Aquatic Resources Management.